Sources and migration characteristics of fluorine in the river water of a small karst watershed influenced by coal mining - Du, Shuangxue; An, Li; Huang, Jiangxun; Li, Qingguang; Wu, Pan; Guo, Xingqiang (Frontiers in Environmental Science, 2022)
In high-fluorine geological background areas, the supergene geochemical process of fluorine has an impact on regional environmental health and safety, which has long been the focus of attention. However, in karst areas characterized by a high incidence of endemic fluorosis, the migration and transformation of fluorine in surface water have not received sufficient attention. This study investigated the joint influence of the weathering and erosion of carbonate rocks and coal-bearing strata on a typical small watershed. Accordingly, 239 samples representing 13 periods of hydrochemical samples were systematically collected to clarify the source, migration, and transformation characteristics of fluorine in surface water. The results revealed that the pH of the Huatan River was low in the rainy season and high in the dry season. The annual variation range of fluorine concentration was 0.11–0.40 mg/L. Although mining development produced acid mine drainage with high fluorine concentration, its impact at the watershed scale appeared to be limited. In terms of spatial scale, the concentration of fluorine in the Huatan River increased gradually from upstream to downstream. The dissolution of fluorite and other fluorine-bearing minerals had not reached the saturation state. The fluorine in the watershed primarily came from the dissolution of fluorine-bearing minerals, followed by the contribution of atmospheric precipitation. The release of fluorine adsorbed on the surface of clay minerals was not the main source of this element. The leaching of the watershed was shown to represent a critical transport process concerning fluorine in the Huatan River, and evaporation had a notable impact on the enrichment of fluorine in water.